Comparative efficacy and safety of prostacyclin therapies for pulmonary arterial hypertension: a systematic review and network meta-analysis - Saleh, Khaled M.; Mallat, Jihad; Mohammed, Samiuddin; Bodi, Govinda; Alazazzi, Hosam; Salim, Simi; Elhennawi, Mohamed; Iqbal, Talha; Sabbour, Hani (Frontiers in Medicine, 2025)
BackgroundPulmonary arterial hypertension (PAH) is a progressive, fatal cardiopulmonary disorder characterized by elevated pulmonary vascular resistance leading to right heart failure. Current treatment utilizes pathway-specific vasodilators, including numerous prostacyclin therapies with diverse delivery methods. Despite available options, head-to-head studies comparing these treatments remain scarce.AimThis network meta-analysis seeks to systematically evaluate all prostacyclin-based PAH therapies to guide clinical decision-making regarding treatment selection.MethodsWe implemented a frequentist approach to network meta-analysis (NWM). For continuous outcomes, we calculated pooled mean differences (MD), whereas risk ratios (RR) were determined for binary endpoints. All estimates incorporated 95% confidence intervals. Results achieving p-values below 0.05 were considered statistically significant.ResultsOur NWM comprising 32 studies (N = 7,819) revealed significant mortality reduction with treprostinil versus placebo (RR 0.66, 95%CI 0.49–0.90), while epoprostenol transitioned demonstrated superior survival benefit (P-score 0.78). For functional capacity, epoprostenol exhibited the greatest 6-Minute Walking Distance (6MWD) improvement (46.84 m, 95%CI 21.90–71.78; P-score 0.90) versus placebo. Hemodynamically, epoprostenol achieved optimal Pulmonary Arterial Pressure (PAP) reduction (−6.29 mmHg, 95%CI -6.99 to −5.59; P-score 0.95), while iloprost demonstrated superior Pulmonary Vascular Resistance (PVR) improvement (−342.09, 95%CI -410.30 to −273.87; P-score 1.00). Epoprostenol ranked highest for Right Atrial Pressure (RAP) reduction (−2.41 mmHg, 95%CI -2.65 to −2.18) and cardiac index improvement (0.56, 95%CI 0.49–0.63). Regarding clinical worsening, selexipag showed potential superiority (RR 0.62, 95%CI 0.51–0.74; P-score 0.95) compared to treprostinil (P-score 0.55).ConclusionOur NMA demonstrates that prostacyclin pathway therapies offer benefits in PAH management. While epoprostenol exhibits superior improvements in hemodynamics and functional capacity, treprostinil reduces mortality by 34%, and selexipag excels in preventing clinical worsening and hospitalizations.